The drivers of export product diversification in China: does natural resource endowments matter? - Ul-Haq, Jabbar; Visas, Hubert; Krivins, Anatolijs; Remeikienė, Rita; Hye, Qazi Muhammad Adnan (Technological and Economic Development of Economy, 2025)
Export product diversification (EPD) mitigates a country’s vulnerability to global trade shocks, contributes to its high-quality economic progress, and increases its resilience. Natural resource endowment (NRE) is considered as one of the important determinants of EPD that is less explored by scholars. The contribution of NRE to EPD will remain a matter of debate in China. The paper aims to identify the drivers of the diversification of export products in China using the province level data from 2011 to 2019. It considers key determinants including foreign direct investment (FDI), human capital (HC), technological innovation (TI), and trade openness (TO). The results of the Fixed Effect-Driscoll-Kraay standard errors (FE-DKSE) indicate a positive and significant relationship between NRE and EPD. This suggests that a rise in NRE within a country promotes EPD. Furthermore, FDI, TO, TI, and HC have statistically significant positive links with EPD. Moreover, the findings of our research are consistent across all regions. The robustness analysis provides evidence that our findings are both significant and robust. The empirical findings indicate that the included variables are fundamental determinants of EPD, which provides policymakers with crucial policy implications. To encourage EPD, the government should implement policies that stimulate these determinants. First published online 05 February 2025